Exploratory Study of Oil Palm Shell as Partial Sand Replacement in Concrete - Khairunisa, Muthusamy; N. A., Zulkepli; Fadzil, Mat Yahaya (Maxwell Scientific Organization, 2013)
Malaysia being one of the world largest palm oil producers has been disposing oil palm shell, which is a by-product from palm oil mill thus causing negative impact to the environment. At the same time, extensive mining of natural river sand in large amount to meet the increasing demand of concrete production for the use in rapidly developing construction industry has posed the risk of natural aggregate depletion and ecological imbalance in future. The effect of finely Crushed Oil Palm Shell (COPS) as partial sand replacement material in concrete mix towards density and compressive strength was investigated in this study. Total of five mixes consisting various content of crushed oil palm shell as partial sand replacement ranging from 0, 25, 50, 75 and 100% were prepared in form of cubes. All the specimens were water cured before tested at 7, 14 and 28 days. Compressive strength was conducted in accordance to BSEN 12390. Generally, the compressive strength and density decrease with the increase in the crushed oil palm shell replacement level. Between 50 to 75% replacement, the mix produced possess lower density enabling it to be categorized as lightweight concrete and has the potential to be used as non-load bearing structure. The application in structural concrete material is suited for mix consisting around 25% of crushed oil palm shell.